Gamma-irradiation produces active chlorine species (ACS) in physiological solutions: Secoisolariciresinol diglucoside (SDG) scavenges ACS - A novel mechanism of DNA radioprotection - Mishra, Om P. (Biochim Biophys Acta, 2016)
BACKGROUND: Secoisolariciresinol diglucoside (SDG), the main lignan in whole grain flaxseed, is a potent antioxidant and free radical scavenger with known radioprotective properties. However, the exact mechanism of SDG radioprotection is not well understood. The current study identified a novel mechanism of DNA radioprotection by SDG in physiological solutions by scavenging active chlorine species (ACS) and reducing chlorinated nucleobases. METHODS: The ACS scavenging activity of SDG was determined using two highly specific fluoroprobes: hypochlorite-specific 3′-(p-aminophenyl) fluorescein (APF) and hydroxyl radical-sensitive 3′-(p-hydroxyphenyl) fluorescein (HPF). Dopamine, an SDG structural analog, was used for proton (1)H NMR studies to trap primary ACS radicals. Taurine N-chlorination was determined to demonstrate radiation-induced generation of hypochlorite, a secondary ACS. DNA protection was assessed by determining the extent of DNA fragmentation and plasmid DNA relaxation following exposure to ClO(−) and radiation. Purine base chlorination by ClO(−) and γ-radiation was determined by using 2-aminopurine (2-AP), a fluorescent analog of 6-aminopurine. Results: Chloride anions (Cl(−)) consumed >90% of hydroxyl radicals in physiological solutions produced by γ-radiation resulting in ACS formation, which was detected by (1)H NMR. Importantly, SDG scavenged hypochlorite- and γ-radiation-induced ACS. In addition, SDG blunted ACS-induced fragmentation of calf thymus DNA and plasmid DNA relaxation. SDG treatment before or after ACS exposure decreased the ClO(−) or γ-radiation-induced chlorination of 2-AP. Exposure to γ-radiation resulted in increased taurine chlorination, indicative of ClO(−) generation. NMR studies revealed formation of primary ACS radicals (chlorine atoms (Cl(•)) and dichloro radical anions (Cl(2)(−•))), which were trapped by SDG and its structural analog dopamine. CONCLUSION: We demonstrate that γ-radiation induces the generation of ACS in physiological solutions. SDG treatment scavenged ACS and prevented ACS-induced DNA damage and chlorination of 2-aminopurine. This study identified a novel and unique mechanism of SDG radioprotection, through ACS scavenging, and supports the potential usefulness of SDG as a radioprotector and mitigator for radiation exposure as part of cancer therapy or accidental exposure.